Letter from J. Ross Snowden to James Curtis Booth, May 4, 1855 - Snowden, James Ross (1855)
James Ross Snowden (1809-1878), director of the United States Mint, writes James Curtis Booth (1810-1888) with news of another lay-off of workers due to a duminished supply of bullion.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States; Precious metals; Snowden, James Ross, 1809-1878